Effectiveness of English language e-learning among tertiary education students during the COVID-19 pandemic - Khairul Faiz Alimi; Abdul Halim Ayob; Abdurraouf Ramesh Abdullah; Fazal Mohamed Mohamed Sultan; Gunasegaran Karuppannan (Penerbit Universiti Kebangsaan Malaysia, 2021)
The unprecedented global pandemic Covid-19 has changed our lives. The pandemic has also impacted the education sector. The significant change of educational methods from face-to-face learning to e-learning has undoubtedly resulted in a significant impact on the perceptions and effectiveness of e-learning among English language learners. This research is to ascertain the perceptions and effectiveness of learning English via elearning through online surveys involving 337 students from a public university in Malaysia. The result on perceptions indicates that flexibility, freedom and interactivity are the reasons why students have positive inclinations towards e-learning, whilst less interaction with teachers, technical problems, and lack of conducive learning experience are the negative perceptions indicated by respondents. The result on the effectiveness of learning English via e-learning shows those students responded positively in learning writing, reading, listening and speaking. Generally, students were both impartial, and enjoyed e-learning. It is hoped that this research would broaden and widen the spectrum of e-learning among students during the pandemic.